2020
DOI: 10.1073/pnas.1921618117
|View full text |Cite
|
Sign up to set email alerts
|

PEBP1 acts as a rheostat between prosurvival autophagy and ferroptotic death in asthmatic epithelial cells

Abstract: Temporally harmonized elimination of damaged or unnecessary organelles and cells is a prerequisite of health. Under Type 2 inflammatory conditions, human airway epithelial cells (HAECs) generate proferroptotic hydroperoxy-arachidonoyl-phosphatidylethanolamines (HpETE-PEs) as proximate death signals. Production of 15-HpETE-PE depends on activation of 15-lipoxygenase-1 (15LO1) in complex with PE-binding protein-1 (PEBP1). We hypothesized that cellular membrane damage induced by these proferroptotic phospholipids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 60 publications
8
69
0
Order By: Relevance
“…As a possibility, changes in membrane PEBP1-dependent lipid signals determine the dual function of autophagy in ferroptosis. 112 , 122 …”
Section: Degradation Systemsmentioning
confidence: 99%
“…As a possibility, changes in membrane PEBP1-dependent lipid signals determine the dual function of autophagy in ferroptosis. 112 , 122 …”
Section: Degradation Systemsmentioning
confidence: 99%
“…It was speculated that autophagy is an indispensable physiological phenomenon in the process of ferroptosis in cells 36 .Wei et al reported that arsenic could damage mitochondria and induce pancreatic dysfunction and ferroptosis via mitochondrial ROS and autophagy-lysosomal disorder 37 . However, Zhao also found that 15-lipoxygenase-1-PE-binding protein-1-generated ferroptotic phospholipids and 15-proferroptotic hydroperoxy-arachidonoyl-phosphatidylethanolamines promoted LC3-I lipidation to stimulate autophagy 38 . This concurrent activation of autophagy protects cells from ferroptotic death and the release of mitochondrial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This concurrent activation of autophagy protects cells from ferroptotic death and the release of mitochondrial DNA. Therefore, when there is an excess of iron ions, the autophagy rate decreases, leading to ferroptotic death 38 . In addition, Liu et al provided novel evidence that the interplay between the signals of the mechanistic target of rapamycin kinase and GPX4 modulates autophagy-dependent ferroptosis in human pancreatic cancer cells, and the down-regulation for GPX4 enhances the anti-cancer activity of rapamycin in vitro or in vivo by promoting ferroptosis and suppressing autophagy 39 .…”
Section: Discussionmentioning
confidence: 99%
“…There are strong indications that PEBPs are involved in regulating autophagy-associated degradation (Noh et al, 2016; Zhao et al, 2020a). Human PEBP1 is reported to interact with LC3-interacting region (LIR) motif of PE-unconjugated LC3B, the homolog of ATG8 in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…The complex prevents the initiation of autophagy that is independent of MAPK signaling pathway (Noh et al, 2016). Moreover, human PEBP4 is co-localized with the lysosome, suggesting its potential role in regulation of degradation (Zhao et al, 2020a). Similarly, whitefly PEBP4 predictably consists of LIR motifs, capable of sequestering ATG8.…”
Section: Discussionmentioning
confidence: 99%